Design and experiment of a jetting dispenser with compact amplifying mechanism and low stress in piezostack. (March 2020) - Wang, Lingyun; Huang, Xiang; Lin, Siying; Bu, Zhenxiang; Jin, Hang; Lin, Xiaolong; Lin, Zhihong; Xie, Peiqin
This article introduced a piezostack-driven jetting dispenser for a microelectronic packaging process. The dispenser had a compact displacement amplification module using two piezostack actuators for achieving compact design and maintaining high jetting performance and improving internal stress on the piezostack actuators. In this article, a working principle of a jetting dispenser configuration was introduced and was followed by the presentation of a displacement amplification mechanism using a cylindrical pivot. The dimensions of the amplification mechanism were determined based on a theoretical calculation of the system and the finite element analysis results. The internal stress of the piezostack and the output displacement of the dispenser were investigated at different operational frequencies. The experimental system with the jetting dispenser was manufactured, and the system performance was verified experimentally. For evaluating the performance, a mixed glycerol/ethanol was used for the dispensing fluid. The jetting system in this study achieved an ideal jetting performance at a jetting frequency of 350 Hz and a droplet diameter of 0.42 mm.